Motion resistance measurements on large lug tyres. (April 2020) - Becker, Carl; Els, Schalk
Highlights: Measuring the motion resistance of large lug tyres. Very low longitudinal force measurements compared to large vertical loads on tyres. Motion resistance measured with drawbar pull, coast down, drum and trailer tests. Compare the measured motion resistance results on the same tyre with four different methods. Investigating the effect that tyre inflation pressure and operating speed has on motion resistance measurements. Abstract: Motion resistance of tyres directly contribute to the operational costs of all vehicles. Advances in the design and simulation of large off-road vehicles (construction, mining, agriculture etc.) have increased the need for accurate models of large off-road tyres. Vehicle OEMs use coast down and drawbar pull tests to determine the motion resistance of tyres used. Drum test rigs and motion resistance test trailers can also be used to determine motion resistance. Most research on motion resistance to date have been conducted on passenger car tyres with on-road truck tyres coming into focus. Motion resistance studies on agricultural tyres traversing over deformable terrain have been conducted in the past. However as more off-road vehicle are being used on-road OEMs of off-road vehicle are infesting in motion resistance measurements on non-deformable terrain. This paper compares different methods used to measure the motion resistance of a large lug tyre, as used in agricultural applications, on non-deformable terrain. Some basic considerations that need to be taken into account are the very low longitudinal forces that need to be measured compared to the large vertical load carried by the tyre and tyre operating conditions.